The Role of Parents in the Nutritional Status of Toddler in Nutritional Conscious Families - Widyaningsih, Tri Sakti; Kanita, Maria Wisnu; Wulandari, Novita Kurnia (Indonesian Journal of Global Health Research, 2024)
A Nutrition Aware Family is a family with balanced nutritional behavior that is able to recognize, prevent and overcome nutritional problems in each member of the family. Objective: This study aims to determine the relationship between the role of parents and the nutritional status of toddlers in nutrition conscious families in Banyuanyar sub-district. This type of research is correlational analytic, using an analytical observation design with a cross-sectional approach. The population in this study was all 65 children under 5 years of age who live in RW 12, Banyuanyar Village. The sampling technique used accidental sampling where the subjects taken as respondents were subjects who were met or happened to come to the service at Posyandu RW 12, Banyuanyar Village, Surakarta City. Data collection was carried out using an instrument in the form of a questionnaire regarding the assessment of families' nutritional awareness with behavioral indicators, namely measuring body weight regularly, giving exclusive breast milk, consuming a variety of foods, using iodized salt and consuming nutritional supplements as recommended. Apart from the questionnaire, researchers used observation sheets of the results of anthropometric measurements of toddlers, namely weight, height and age of toddlers. Measurements using Microtoise, measuring table, scales and metline. The results of the analysis using the Chi square test showed that Kadarzi's behavior of regularly weighing his body had a p value of 0.037, a p value of 0.000 for giving exclusive breast milk and a p value of 0.021 for giving a variety of foods. This research can be concluded that there is a significant relationship between Kadarzi behavior and the nutritional status of toddlers at Posyandu Medang Kamolan RW 12 is an important indicator in nutritionally aware families related to the nutritional status of toddlers.